Comparative Transcriptome Profiling of mRNA and lncRNA of Ovaries in High and Low Egg Production Performance in Domestic Pigeons (Columba livia) - Mao, Haiguang; Xu, Xiuli; Cao, Haiyue; Dong, Xinyang; Zou, Xiaoting; Xu, Ningying; Yin, Zhaozheng (Frontiers in Genetics, 2021)
Egg production performance is one of the most important economic traits in pigeon industry. However, little is known regarding how egg production performance is regulated by long noncoding RNAs (lncRNAs) in pigeons. To evaluate the lncRNAs and mRNAs in ovaries associated with egg production performance in domestic pigeons, high-throughput RNA sequencing of ovaries between high and low egg production performance groups were performed and analyzed in this study. A total of 34346 mRNAs and 24601 lncRNAs were identified, including 14525 known lncRNAs and 10076 novel lncRNAs, of which 811 mRNAs and 148 lncRNAs (P<0.05) were significantly differentially expressed (DE) between the groups of high and low egg production performance. GO and KEGG annotation analysis indicated that the target genes of DE lncRNAs and DE mRNAs were related to cell differentiation, ATP binding and methylation. Moreover, we found that FOXK2, a target gene of lncRNA MSTRG.7894.4, was involved in regulating estrogen receptors. Our study provided a catalogue of lncRNAs and mRNAs associated with egg production performance, and they deserve further study to deepen the understanding of biological processes in the ovaries of pigeons.